No evidence of an association between mitochondrial DNA variants and osteoarthritis in 7393 cases and 5122 controls. Issue 1 (14th September 2012) - Hudson, Gavin; Panoutsopoulou, Kalliope; Wilson, Ian; Southam, Lorraine; Rayner, Nigel W; Arden, Nigel; Birrell, Fraser; Carluke, Ian; Carr, Andrew; Chapman, Kay; Deloukas, Panos; Doherty, Michael; et al.
Abstract : Objectives: Osteoarthritis (OA) has a complex aetiology with a strong genetic component. Genome-wide association studies implicate several nuclear genes in the aetiology, but a major component of the heritability has yet to be defined at the molecular level. Initial studies implicate maternally inherited variants of mitochondrial DNA (mtDNA) in subgroups of patients with OA based on gender and specific joint involvement, but these findings have not been replicated. Methods: The authors studied 138 maternally inherited mtDNA variants genotyped in a two cohort genetic association study across a total of 7393 OA cases from the arcOGEN consortium and 5122 controls genotyped in the Wellcome Trust Case Control consortium 2 study. Results: Following data quality control we examined 48 mtDNA variants that were common in cohort 1 and cohort 2, and found no association with OA. None of the phenotypic subgroups previously associated with mtDNA haplogroups were associated in this study. Conclusions: We were not able to replicate previously published findings in the largest mtDNA association study to date. The evidence linking OA to mtDNA is not compelling at present.